TPACK MODEL IN DEGREE STUDIES FOR INITIAL TEACHER TRAINING IN ICT - ISABEL Mª GÓMEZ TRIGUEROS (Didáctica Geográfica)
Under the abbreviation TPACK we mention the acronym of “Technological Pedagogical Content Knowledge” (TPCK or TPACK) is made. It is a model of teaching and learning (E-A) that identifies the types of knowledge that a teacher needs to master to integrate the Information and Communication Technologies (ICT) in an effective way in imparting education. It is included among the cognitive models in cooperative environments, where, in addition, the technology is used. The pioneers in implementing this model are teachers Punya Mishra and Matthew J. Koehler, of Michigan State University (between 2006 and 2009).